Features of improving the methodical training system of future teachers - Fahriddin Orinboevich Tashboltaev (Zien Journals, 2022)
This article examines the specifics, principles and aspects of improving the system of methodological training of future teachers, reinforced by legislative and other regulatory foundations
Keywords: methodical training; training; form; method